Urinary Tract Infections in Women of Child Bearing Age - Razzak, Sadaf; Sami, Farhana; Lohana, Muskan; Athar, Jannat; Kumari, Sona; Kalwar, Sundas (Journal of Postgraduate Medical Institute, 2025)
Objective: The study aimed to assess the frequency and risk factors of urinary tract infections (UTIs) among women of childbearing age and evaluate the association between age, anemia, and UTI prevalence in patients attending the Gynaecology and Obstetrics Clinic at a tertiary care hospital in Karachi. Methodology: A cross-sectional study was conducted among 91 women aged 18-45 years. Data was collected using a structured online questionnaire and analyzed through SPSS version 20.0. Descriptive statistics and the chi-square test were applied to assess the association between anemia severity, age groups, and UTI occurrence, with p<0.05 considered statistically significant. Results: The frequency of UTI in this population was found to be 37% (n=34). Among symptomatic cases, the most common initial symptom was burning micturition (26.4%, n=24), followed by increased frequency of urination (22%, n=20). The most prevalent microorganism identified in UTI cases was Escherichia coli (73%, n=66), followed by Klebsiella spp. (12%, n=11), Proteus mirabilis (8%, n=7), Pseudomonas aeruginosa (5%, n=5), and Staphylococcus aureus (2%, n=2). A significant proportion of women (46.2%, n=42) were mildly anemic, and anemia was found to be significantly associated with UTI (p < 0.001). Additionally, the majority of women belonged to middle socioeconomic status (65%, n=59), which also showed a significant association with UTI. Conclusion: UTI remains a prevalent health issue among women of childbearing age. Significant risk factors include anemia, socioeconomic status, and post-coital voiding habits. The identification of Escherichia coli as the most common causative agent suggests the need for targeted antibiotic strategies. Increased awareness of hygiene practices and timely medical consultations can help mitigate the risk of UTIs in this population.